On Maintenance and Development of Administrative Education - V. M. Serov (Управление)
This article gives a brief assessment of the current management education crisis and presents the author’s approach to its maintenance and development, based on the assumption that the management objects are technical, socio-economic systems, and socio-political processes. Accordingly, the requirements for the maintenance of curriculums of the trainings for the management specialists in the university, the ratio of the technical-technological disciplines in economics, organization and production management, socio-political relations organization and management are determined. The post-graduate management education is also considered.